Development of an Experimental Environment Based on a Helmholtz Cage for the Validation of Satellite Attitude Control Systems (2025)
Attitude control is essential for the operation of satellites, especially in low-cost missions that employ compact technologies such as magnetorquers. To validate these systems, a ground based testing environment capable of accurately simulating the magnetic field to which the satellite will be exposed during operation is required. Currently, the University of Antioquia has a Helmholtz cage that can generate a homogeneous magnetic field; however, it has not yet been integrated into a functional testing environment. This project aims to implement and verify an experimental environment based on a Helmholtz cage for the evaluation of atti tude control systems. Initially, the magnetic field generated by the cage will be characterized to identify its effective testing area. Then, orbital simulations will be performed to obtain the satellite’s position and calculate the magnetic field of the Earth to which it is exposed, which will then replicate in the cage through a voltage control system that ensures fidelity in the testing environment. In addition, a test platform will be developed, including the ins trumentation, circuitry, and test protocols necessary to use the Helmholtz cage. This project not only addresses a technical challenge but also establishes a solid foundation for future research and academic activities related to satellite attitude control and the improvement of the experimental environment.